STUDENTS’ PERSPECTIVE:LECTURE’S TEACHING STYLE IN THE CLASS AT ENGLISH DEPARTMENT AT MUHAMMADIYAH UNIVERSITY BONE - Fahriadi Muhdar; Sirwanti Sirwanti; Dian Riani Said; Serlindayanti Serlindayanti (Journal of Innovation Research and Knowledge, 2022)
The study of teaching style is needed to provide several contributions to teachers and prospective teachers in teaching. The purpose of this study was to find out the type of teaching style of lecturers conducted in English department. The subject of the research was English department at which consists of 16 students. The research use qualitative method. The instruments to collect the data were observation checklist and questionnaire. The result of the research showed that there are 10 item main types of teaching style which are, The expert type, formal authority, personal, facilitator type, the elementary, intermediate, creative / intractional, Democratic, Indifferent,classical teaching style with 23 sub items category and there are several new style of taching based on their perspective. Some of the lecturer were use more than one teaching style and it depends on the situation, material that they will present, and their personalities. However most of students fell bored when the leacture always give task by presentation and lecturing.